STRATEGI PENGEMBANGAN DAYA TARIK EKOWISATA AIR TERJUN NYARAI LUBUK ALUNG KABUPATEN PADANG PARIAMAN - Putri, Anisa Ellyza; Wulandari, Dwi Pratiwi (Ensiklopedia of Journal, 2025)
The main problem that exists in this research is the limited or lack of tourist attractions that can be done by visitors at Nyarai Waterfall. The purpose of this research was to determine the strategy for developing the ecotourism attractiveness of Nyarai Lubuk Alung Waterfall with indicators of attraction, accessibility, amenity and ancillary service. The data used is descriptive qualitative. This type of research is a qualitative descriptive research. Qualitative research method is a research method used to examine the condition of natural objects, and researchers as key instruments, data collection techniques are carried out in a triangulation (combined) manner, and data analysis is inductive.               The results of this study indicate that 1) Attraction: providing tourist attractions that are family friendly by utilizing the Batu Tudung location, optimizing rental of equipment used to support tourism activities, as well as providing training to all tour guides so they can guide visitors in bird watching activities. 2) Accessibility: providing shuttle services for visitors who do not bring vehicles, directing visitors to other alternative routes due to road conditions that cannot be passed by all types of vehicles, and road conditions leading to Nyarai Waterfall can be used as a trekking route. 3) Amenities: developing toilet and mushalla facilities because there is a lot of vacant land that can be utilized, providing a place to buy and sell souvenirs so that they can increase the income of the local community, as well as updating road signs to Nyarai Waterfall to make it easier for visitors to visit Nyarai Waterfall. 4) Ancillary Service: provide professional health workers at Nyarai Waterfall, complete the availability of medicines at health posts, and determine certain parties to be selected as security officers at Nyarai Waterfall.                Keywords: Strategy, Development, Ecotourism Attraction